Comparison of Foot Pressure Distribution During Single-leg Squat in Individuals With and Without Pronated Foot - Il-kyu Ahn; Gyeong-tae Gwak; Ui-jae Hwang; Hwa-ik Yoo; Oh-yun Kwon (Korean Research Society of Physical Therapy, 2024)
Background: Single-leg squat (SLS)s are commonly used as assessment tool and closed kinetic exercises are useful for assessing performance of the lower extremities. Pronated feet are associated with foot pressure distribution (FPD) during daily activities. Objects: To compare the FPD during SLSs between groups with pronated and normal feet. Methods: This cross-sectional study included 30 participants (15 each in the pronated foot and control groups) are recruited in this study. The foot posture index was used to distinguish between the pronated foot and control groups. The Zebris FDM (Zebris Medical GmbH) stance analysis system was used to measure the FPD on the dominant side during a SLS, which was divided into three phases. A two-way mixed-model ANOVA was used to identify significant differences in FPD between and within the two groups. Results: In the hallux, the results of the two-way mixed-model ANOVAs revealed a significant difference between the group and across different phases (p < 0.05). The hallux, and central forefoot were significantly different between the group (p < 0.05). Moreover, significant differences across different phases were observed in the hallux, medial forefoot, central forefoot, lateral forefoot, and rearfoot (p < 0.05). The post hoc t-tests were conducted for the hallux and forefoot central regions. In participants with pronated foot, the mean pressure was significantly greater in hallux and significantly lower, in the central forefoot during the descent and holding phases. Conclusion: SLSs are widely used as screening tests and exercises. These findings suggest that individuals with pronated feet should be cautious to avoid excessive pressure on the hallux during the descent-to-hold phase of a SLS.